PREVIDA- IMPACT OF VORTIOXETINE ON MAJOR DEPRESSIVE DISORDER AND PERCEIVED COGNITIVE DYSFUNCTION: A MULTICENTRE STUDY - Mufti, Ali Ahsan; Mughal, Huma; Ul Haq, Mian Mukhtar; Kamal, Muhammad Asif; Rabbani, Fazale; Mufti , Khalid Attaullah; Sultan, Syed Muhammad; Ahmad, Bashir; Nawaz, Zainab; Afridi , Adil; Khan, Fatima Amir; Qasim , Muhammmad Fahim; et al. (Journal of Pakistan Psychiatric Society, 2023)
OBJECTIVE To find out how common cognitive impairment is in people with major depressive disorder (MDD) and assess how well vortioxetine works for treating both cognitive dysfunction and depressive symptoms. Study Design: Multi-centred, Cross-sectional, prospective follow up design Place & Duration of Study: The research took place over the course of 12 weeks at 16 different psychiatric outpatient clinics throughout Pakistan, from September 2020 to November 2020. Method: The study included 498 individuals with serious depressive disorder diagnoses. The degree of depression symptoms and cognitive impairment was assessed. Psychiatrists gave trial participants vortioxetine after completing the Clinical Global Impression-Severity scale (CGI-S), the Patient Health Questionnaire-9 (PHQ-9), and the Perceived Deficits Questionnaire (PDQ). The variables were reassessed one week (+/- 3 days), one month (+/- 7 days), and three months (+/- 14 days) after the treatment began. Results: After completing a 12-week course of therapy with vortioxetine, mean PHQ 9 and PDQ scores of MDD individuals showed significant improvements. This indicates that vortioxetine is effective in reducing depression symptoms as well as cognitive impairments in MDD patients. A strong connection was seen between PHQ-9 and PDQ scores, indicating a direct relationship between cognitive impairment and depressed symptoms. Conclusions: The results of the research demonstrate how well vortioxetine works to treat cognitive impairments in MDD patients while also reducing depressed symptoms. These findings demonstrate the possibility of vortioxetine as a beneficial therapeutic option for those with MDD diagnoses who also have cognitive impairment. Additional investigation is required to validate these findings and assess their suitability for other demographics.